Recovery of citrus triploid hybrids by embryo rescue and flow cytometry from 2x x 2x sexual hybridisation and its application to extensive breeding programs - Aleza, Pablo; Juárez, José; Cuenca, José; Ollitrault, Patrick; Navarro, Luis (2017)
Seedlessness is one of the most important characteristics for mandarins for the fresh-fruit market and mandarin triploid hybrids have this trait. Citrus triploid plants can be recovered by 2x x 2x sexual hybridisations as a consequence of the formation of unreduced gametes at low frequency. Triploid embryos are found in small seeds that do not germinate under greenhouse conditions. Extensive breeding programs based on this type of hybridisation require very effective methodologies for embryo rescue and ploidy evaluation. In this work, we describe an effective methodology to recover triploid hybrids from 2x x 2x hybridisations based on in vitro embryo rescue and ploidy level determination by means of flow cytometry. The influence of parents and environmental conditions on obtaining triploid hybrids has been analysed. The strongest effect was associated with the genotype of the female parent while a strong interaction was found between the male parent genotype and environmental conditions. The effect of the female parent genotype on the length of the juvenile phase was also demonstrated by observing a large number of progenies over the last 10 years. The methodology described here has enabled us to obtain over 4,000 triploid hybrids so far, of which 13 have been protected in the European Union and two are being extensively planted by citrus growers to establish new commercial plots. These triploid hybrids have been analysed with simple sequence repeats markers to differentiate all the new triploid varieties and their parents, and thus molecular identification will help defend plant breeders' rights.